PENGARUH DIFERENSIASI PRODUK DAN SALURAN DISTRIBUSI TERHADAP LOYALITAS PELANGGAN PADA CV. MAKMUR AUTO SEJAHTERA MEDAN - Yulianti; Edwin Sugesti Nasution (Jurnal Manajemen Bisnis Eka Prasetya, 2020)
This study aims to determine the effect of product differentiation on customer loyalty on CV. Makmur Auto Sejahtera Medan, knows the effect of distribution channels on customer loyalty on CV. Makmur Auto Sejahtera Medan, and find out the effect of product differentiation and distribution channels on customer loyalty on CV. Makmur Auto Sejahtera Medan. The population in this study is CV. Makmur Auto Sejahtera Medan as many as 62 permanent customers. The sampling technique in this study used saturated samples. Thus, the number of research samples used was 62 permanent customers. Data were analyzed using the method of multiple linear regression analysis. The results of the analysis give the equation Customer Loyalty = 0,108+ 0,249 Product Differentiation + 0,383DistributionChannels + e. The results of the study partially indicate that product differentiation has a positive and significant effect on customer loyalty CV. Makmur Auto Sejahtera Medan. This is evidenced from the acquisition of tarithmetic 4.834 > ttable 1.67065 and a significant value of 0,000 < 0.05 and the distribution channel has a positive and significant effect on customer loyalty CV. Makmur Auto Sejahtera Medan. This is evidenced from the acquisition of the value of tarithmetic 4.818 > ttable 1.67065 and a significant value of 0.000 < 0.05. Simultaneously, product differentiation and distribution channels simultaneously have a positive and significant effect on customer loyalty CV. Makmur Auto Sejahtera Medan. This is evidenced from the acquisition of the calculated Farithmetic 30,308 > Ftable 3,15 and a significant value of 0,000 < 0.05. Product differentiation and distribution channels can explain customer loyalty by 49.0% and the remaining 51.0% is influenced by other variables outside of this study such as customer satisfaction, brand and price.